MODEL BIMBINGAN AKADEMIK UNTUK PENINGKATAN KETERAMPILAN DAN KEMANDIRIAN BELAJAR MAHASISWA DI PERGURUAN TINGGI - Nurhayati, Eti (2010)
The ideal and real personal developments of university students as well as the system of education at university have intrigued the researcher to undergo this study. The research findings revealed that most of students show low in learning skill and independent learning, academic guidance services need serious improvement, and genuine institutional policy to maximize academic guidance service. Based on that background this research is conducted to produce a model of academic guidance on the basis of the existing problems among the students-low learning skill and less independent learning in the researched site to help them develop their learning skill and independent learning. Research and Development (R&D) model was employed to investigate the issues. It passed four stages: conducting pre-survey, designing draft model, validating draft model, and examining draft model. It used quasi experimental research model using pre-test and post-test non-equivalent control group design. While data collection techniques consist of questionnaire distribution to the respondents to get the information about their levels of learning skill and independent learning, interview for academic advisors to get the data on the available academic guidance services, and interview for institutional manager to get descriptions on policy and support for academic guidance services. The data, then, analyzed using descriptive qualitative, descriptive statistics, and comparison test method. The study significantly shows that the model of academic guidance is effective to enhance student's learning skill and independent learning. It, positively, has proven the hypothesis that: (1) The model of academic guidance enhanced higher level of learning skill of experimental group students than the control group ones; (2) The model of academic guidance enhanced higher level of independent learning of experimental group students than the control group ones. Key Words: Learning skill, Independent Learning, Model of Academic Guidance.